Assessing the situation of disability research in the Philippines : an exploratory study - Muhamad Nadhir Abdul Nasir,; Alfa Nur Aini Erman Efendi,; Rosila Bee Mohd Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper attempts to discuss findings from an exploratory study in respect to the situation of disability research discourse in the Republic of the Philippines. We disseminate qualitative surveys to three key informants in The Philippines that we choose purposively. The three informants consist of a person with visual impairment, a person with speech impairment, and a person with mobility impairment. Responses from our informants reveal there exists a priority gap on disability research production between different stakeholders. We also learn that disability research produces benefits both in micro and macro contexts. Informants also claim to face barriers in accessing local disability research. Concerns are also being made in regards to emancipatory impact of local disability research as well as for competency and commitment by local researchers. We conclude this paper by stressing the importance of disability studies scholarship development in Southeast Asian region and aggressive effort is needed to merge the academic, political and public spheres to empower the disabled community.